Higiene Dan Sanitasi Pengelolaan Makanan Dan Kepadatan Lalat Pada Warung Makan Di Pasar Tradisional Pasar Horas Pematangsiantar Tahun 2013 - Devi Justika Sembiring, Taufik Ashar dan Wirsal Hasan (Lingkungan dan Kesehatan Kerja, 2014)
The hygiene and sanitation of food processing and flies density at the eatery in the traditional market Pasar Horas Pematangsiantar 2013. Eatery is a commercial bussines that provides food and beverage for public society. Food sanitation hygiene purpose is managing food of avoiding to become source of disease. This research aims to find out about hygiene of Eatery in Pasar Horas Pematangsiantar city according to the staff character, sanitation hygiene principal of food processing, food delivery, finished food storing , food servicing, sanitation facility and the measurement of flies density. This research is a descriptive reseach that explain the sanitation hygine of food management which the datas are obtained by observing and analyzed based on exist theory namely Kepmenkes Ri No. 1098/Menkes/SK/VII/2003 about the required condition the healthy of eatery and restaurant, and measurement of flies density by using Fly Grill and adjusted with interpretation according to health department. This research shows that most of responden education is High school (76.5 %), according to >15 years trading period (47%), 2 to 3 labour of food processing (70.6 %). Applying the sanitation hygiene including food material (100%) has fullfilled the require needed, the other has not fullfilled the requirement incluidng food material storing, food processing, finished food storing, food delivery, food servicing and sanitation facility. Most of the processor and waiter have not fullfilled the principal of food processing. The density of flies (58.8%) is in the medium level (3-5) and the further research need to be done to find out the breeding place. According to the result of the research, it is suggested to do some training and counceling about the hygiene and sanitation in eatery to be better for healt. Keywords : Hygiene Sanitation, Eatery, Flies Density